2014
DOI: 10.4236/ijcm.2014.514111
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Outcome of Bisphosphonate Therapy in Patients with Primary Hyperparathyroidism

Abstract: Context: Primary hyperparathyroidism (PHPT) is commonly associated with reduced bone mineral density (BMD) presenting with osteoporosis, increasing the risk of bone fragility fractures in these patients. Bisphosphonates, due to their anti-resorptive action, are known to improve the BMD and reduce the risk of bone fragility fractures. Therefore, bisphosphonates are considered as an alternative to surgical treatment in managing osteoporosis in PHPT patients. Aim: The aim of this observational study was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Only two out of the three ( 45 , 47 ) reports on s-calcium which is unchanged in one and decreases in the other during treatment, PTH, CTX, and alkaline phosphatase are reported to decline. Vera et al ( 47 ) reports a small and insignificant decline in BMD, whereas Yeh et al and Segula et al ( 45 , 48 ) in accordance with most other studies report an increase at spine and hip. The prior study also reports a markedly increased risk of fractures compared to patients treated surgically (PTX) as well as controls, but the bisphosphonate subgroup also did have a much lower BMD at baseline compared to the other two groups.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Only two out of the three ( 45 , 47 ) reports on s-calcium which is unchanged in one and decreases in the other during treatment, PTH, CTX, and alkaline phosphatase are reported to decline. Vera et al ( 47 ) reports a small and insignificant decline in BMD, whereas Yeh et al and Segula et al ( 45 , 48 ) in accordance with most other studies report an increase at spine and hip. The prior study also reports a markedly increased risk of fractures compared to patients treated surgically (PTX) as well as controls, but the bisphosphonate subgroup also did have a much lower BMD at baseline compared to the other two groups.…”
Section: Resultsmentioning
confidence: 97%
“…The articles concerning etidronate (2) ( 40 , 41 ), risedronate (2) ( 42 , 43 ), neridronate (1) ( 44 ), and mixed bisphosphonates (4) ( 45 48 ) were, due to the limited number of studies, pooled into one group called mixed bisphosphonates (see Table S4 in Supplementary Material). The articles reporting on effects of etidronate, risedronate, and neridronate used one drug only for all included subjects, whereas the articles on mixed bisphosphonates used a variety of different bisphosphonates within the individual study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al reported the can prevent hungry bone syndrome among a very small number of patients [104]. Two other studies reported increase in BMD in the lumbar spine and hip [85,106].…”
Section: Bisphosphonatesmentioning
confidence: 98%